THE USE OF KAPOK SEED AGRICULTURAL WASTE AS A SOURCE OF NATURAL CORROSION INHIBITOR FOR ALUMINUM 6061 - Syarif Hidayatullah; Ahmad Akromul Huda; Suteja Suteja (Protech Biosystems Journal, 2025)
Aluminum 6061 is one of the most widely used materials across various industrial sectors due to its good mechanical properties, lightweight nature, and corrosion resistance. However, in acidic environments, aluminum remains susceptible to corrosion, which can reduce its performance and service life. This study utilizes agricultural waste from kapok seeds (Ceiba pentandra) as an environmentally friendly corrosion inhibitor for Aluminum 6061. The extract was obtained through maceration using ethanol as the solvent and was applied in corrosion tests of Aluminum 6061 in 1 M HCl solution. The evaluation was conducted using potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) techniques, along with isothermal adsorption analysis to understand the adsorption mechanism of the inhibitor on the metal surface. The results showed that the kapok seed extract significantly increased polarization resistance and reduced the corrosion rate, achieving a maximum inhibition efficiency of 78.77% at an optimal concentration of 3000 ppm. The inhibitor adsorption followed the Freundlich isotherm model, indicating strong binding interactions between the inhibitor molecules and the aluminum surface. Therefore, kapok seed extract has great potential as an environmentally friendly and cost-effective corrosion inhibitor for aluminum-based industries.